Bathymetry Beneath the Amery Ice Shelf, East Antarctica, Revealed by Airborne Gravity. Issue 24 (23rd December 2021) - Yang, Junjun; Guo, Jingxue; Greenbaum, Jamin S.; Cui, Xiangbin; Tu, Liangcheng; Li, Lin; Jong, Lenneke M.; Tang, Xueyuan; Li, Bingrui; Blankenship, Donald D.; Roberts, Jason L.; van Ommen, Tas; et al.
Abstract: The bathymetry under the Amery Ice Shelf steers the flow of ocean currents transporting ocean heat, and thus is a prerequisite for precise modeling of ice‐ocean interactions. However, hampered by thick ice, direct observations of sub‐ice‐shelf bathymetry are rare, limiting our ability to quantify the evolution of this sector and its future contribution to global mean sea level rise. We estimated the bathymetry of this region from airborne gravity anomaly using simulated annealing. Unlike the current model which shows a comparatively flat seafloor beneath the calving front, our estimation results reveal a 255‐m‐deep shoal at the western side and a 1, 050‐m‐deep trough at the eastern side, which are important topographic features controlling the ocean heat transport into the sub‐ice cavity. The new model also reveals previously unknown depressions and sills that are critical to an improved modeling of the sub‐ice‐shelf ocean circulation and induced basal melting. Plain Language Summary: The ocean currents are strongly steered by the seafloor topography. Therefore, the seafloor topography should be represented at fine resolution to study how the warm water melts the ice shelf from below. However, the seafloor beneath the largest ice shelf in East Antarctica remains poorly known, because the thick floating ice blocks direct bathymetric observations. We used gravity measured by airplane to infer the shape of the seafloor beneath the floating ice. The gravity‐inferred seafloor topography model is substantially improved over the existing BedMachine Antarctica model, and reveals previously unknown topographic features. The newly identified seafloor topographic features could improve our knowledge about how much ocean heat enters the sub‐ice cavity and how the ocean currents flow beneath the ice shelf. With this knowledge, scientists could more accurately project the response of the Amery Ice Shelf to ocean forcing and this region's future contribution to global mean sea level rise. Key Points: The seafloor topography beneath the Amery Ice Shelf, East Antarctica, is estimated from airborne gravity using simulated annealing Estimation results present updated ice front geometry, an important factor controlling the ocean heat transport into sub‐ice cavity The model reveals previously unknown depressions at the western flank that are critical to an improved modeling of ocean circulation